'Lines of Flight or Tethered Wings'?: A Deleuzian Analysis of Women-specific Adventure Skills Courses in the United Kingdom. (December 2021) - Avner, Zoë; Boocock, Emma; Hall, Jenny; Allin, Linda
Abstract : In this article we examine women-specific adventure sport skills training courses in the UK utilising a feminist new materialist approach. Drawing on Gilles Deleuze and Félix Guattari's (1987) concepts of 'assemblage', 'lines of territorialisation', and 'lines of flight', we apply a new lens to ask: what type(s) of material-discursive assemblages are produced through human and non-human, discursive, and non-discursive intra-actions on women-specific adventure sport skills courses? To what extent do these courses enable participants to engage with an alternative praxis and ethics and to think, feel, practice, and become otherwise? Our Deleuzian reading showed that the affective capacity of these courses is currently limited by dominant understandings of these courses as bridges to the real outdoors and as primarily designed for women who lack the confidence to participate in mixed-gender environments. However, these courses also enabled productive lines of flight and alternative understandings and practices related to the self, the body, others, material objects, learning, movement, and physical activity to emerge. These were both characterised and supported by less instrumental and hierarchical flows of relations and an openness to not knowing.